The landscape of the Gospels: a deeper meaning - Senior, Donald (Biblical studies from the Catholic Biblical Association of America, 2020)
"The Landscape of the Gospels explores the geography of the gospel narratives and the Acts of the Apostles and reveals the deeper meaning that this often overlooked dimension gives the biblical texts"--